Mobility of metal(loid)s in Pb/Zn tailings under different revegetation strategies. (1st June 2020) - Wang, Guobao; Zhao, Wanying; Yuan, Yongqiang; Morel, Jean Louis; Chi, Haochun; Feng, Wenling; Wang, Shizhong; Zhang, Jianxiang; Feng, Zekai; Tan, Haoran; Chen, Daijie; Ding, Wenge; et al.
Abstract: Metal tailings are potential sources of strong environmental pollution. In situ remediation involves the installation of a plant cover to stabilize materials and pollutants. Whether metal(loid)s are effectively immobilized in remediated tailing ponds submitted to heavy rainfall remains uncertain. In this study, tailing materials were collected from bare tailings (control), grass-planted (G) and grass-shrub planted (GS) areas on a former Pb/Zn mine site. Batch column experiments were performed with three rainfall intensities of 0.36, 0.48, and 0.50 mL min −1 for 18 d in the lab. The pH, Eh, Cd, Pb, Zn and As concentration in leachate were recorded. Selected leached tailing materials were finally characterized. Results showed that leachates from control were strongly acidic (pH 3.11–4.65), and that Cd, Pb, Zn and As were quickly released at high rate ( e.g ., 945 mg L −1 Zn). During the experiment up to 4% Cd present in the material was released and almost 1% Zn. With material collected from the G area, leachates were even more acidic (2.16–2.84) with a rainfall intensity of 0.50 mL min −1 and exhibited a high redox potential (588–639 mV). However, concentrations of metals in leachates were much lower than that in the control, except for Zn ( e.g ., 433 mg L −1 ), and they tended to decrease with time. Cumulative leaching rate was still relatively high ( e.g ., 0.68% Cd; 0.75% Zn) during the first eight days (stage I). However, with the GS treatment, leachate pH gradually raised from acid to alkaline values (3.9–8.2) during stage I, then remained high until the end of the experiment (stage II). Also, amounts of elements released during the 18 d were low in general. The releasing ratios of Cd ( R 2  > 0.95), Pb ( R 2  > 0.95), As ( R 2  > 0.87), and Zn ( R 2  > 0.90) fitted well with a two-constant model. In conclusion, under subtropical climate with heavy rainfall, phytostabilization is effective but immobilization of metals is higher with a combination of grass and shrub than with only grass to reduce leaching of As and Zn. Graphical abstract: Image 1 Highlights: Cumulative leaching rates of Cd, Pb, Zn and As increased with rainfall intensities. Grass-shrub planted strategy shows better effect on metal(loid) immobilization. Leachate pH and tailing carbon increased under grass-shrub planted strategy.